Interpreting seasonal changes in the carbon balance of southern Amazonia using measurements of XCO2 and chlorophyll fluorescence from GOSAT - Parazoo, Nicholas C.; Butz, André (Geophysical research letters, 2013)
Amazon forests exert a major influence on the global carbon cycle, but quantifying the impact is complicated by diverse landscapes and sparse data. Here we examine seasonal carbon balance in southern Amazonia using new measurements of column-averaged dry air mole fraction of CO2 (XCO2) and solar induced chlorophyll fluorescence (SIF) from the Greenhouse Gases Observing Satellite (GOSAT) from July 2009 to December 2010. SIF, which reflects gross primary production (GPP), is used to disentangle the photosynthetic component of land-atmosphere carbon exchange. We find that tropical transitional forests in southern Amazonia exhibit a pattern of low XCO2 during the wet season and high XCO2 in the dry season that is robust to retrieval methodology and with seasonal amplitude double that of cerrado ecosystems to the east (4 ppm versus 2 ppm), including enhanced dilution of 2.5 ppm in the wet season. Concomitant measurements of SIF, which are inversely correlated with XCO2 in southern Amazonia (r = −0.53, p < 0.001), indicate that the enhanced variability is driven by seasonal changes in GPP due to coupling of strong vertical mixing with seasonal changes in underlying carbon exchange. This finding is supported by forward simulations of the Goddard Chemistry Transport Model (GEOS-Chem) which show that local carbon uptake in the wet season and loss in the dry season due to emissions by ecosystem respiration and biomass burning produces best agreement with observed XCO2. We conclude that GOSAT provides critical measurements of carbon exchange in southern Amazonia, but more samples are needed to examine moist Amazon forests farther north.